TEACHER'S STRATEGIES IN OVERCOMING STUDENTS' DIFFICULTIES IN READING COMPREHENSION OF NARRATIVE TEXTS - Wati, Yulia Vera (2015)
The research entitled Teacher's Strategies in Overcoming Students' Difficulties' in Reading Comprehension of Narrative Texts is a case study research conducted at the eighth grade of a boarding school in Bandung Regency. This research aims to find out what difficulties faced by the students in reading comprehension of narrative text and what strategies used by the teacher to overcome those difficulties. The research was conducted in a class which consisted of 20 participants and 15 of them were taken as the samples. Thedata in this study were obtained from task-giving, interview and observation. The findings revealed that the students faced some difficulties in reading comprehension of narrative texts; limited vocabulary knowledge, problems with processing information, and problems in recalling information after reading. To overcome those difficulties, the teacher used some strategies; repeat the word, describe and support with visual, connected words to students' lives. Based on this research, it is suggested that those teacher's strategies can be used at school to improve students' reading comprehension. Keywords: Students' difficulties, teacher's strategies, reading comprehension